Creation of an open-access, mutation-defined fibroblast resource for neurological disease research. - Selina Wray; Matthew Self; NINDS Parkinson's Disease iPSC Consortium; NINDS Huntington's Disease iPSC Consortium; NINDS ALS iPSC Consortium; Patrick A Lewis; Jan-Willem Taanman; Natalie S Ryan; Colin J Mahoney; Yuying Liang; Michael J Devine; Una-Marie Sheerin; et al. (PLoS ONE)
Our understanding of the molecular mechanisms of many neurological disorders has been greatly enhanced by the discovery of mutations in genes linked to familial forms of these diseases. These have facilitated the generation of cell and animal models that can be used to understand the underlying molecular pathology. Recently, there has been a surge of interest in the use of patient-derived cells, due to the development of induced pluripotent stem cells and their subsequent differentiation into neurons and glia. Access to patient cell lines carrying the relevant mutations is a limiting factor for many centres wishing to pursue this research. We have therefore generated an open-access collection of fibroblast lines from patients carrying mutations linked to neurological disease. These cell lines have been deposited in the National Institute for Neurological Disorders and Stroke (NINDS) Repository at the Coriell Institute for Medical Research and can be requested by any research group for use in in vitro disease modelling. There are currently 71 mutation-defined cell lines available for request from a wide range of neurological disorders and this collection will be continually expanded. This represents a significant resource that will advance the use of patient cells as disease models by the scientific community.